SLFL Genes Participate in the Ubiquitination and Degradation Reaction of S-RNase in Self-compatible Peach - Chen, Qiuju; Meng, Dong; Gu, Zhaoyu; Li, Wei; Yuan, Hui; Duan, Xuwei; Yang, Qing; Li, Yang; Li, Tianzhong (Frontiers in Plant Science, 2018)
It has been proved that the gametophytic self-incompatibility (GSI) of Rosaceae, Solanaceae and Plantaginaceae is controlled by two tightly linked genes located at highly polymorphic S-locus: the S-RNase for pistil specificity and the F-box gene (SFB/SLF) for pollen specificity, respectively. However, the roles of those genes in SI of peach are still a subject of extensive debate. In our study, we selected 37 representative varieties according to the evolution route of peach and identified their S genotypes. We cloned pollen determinant genes mutated PperSFB1m, PperSFB2m, PperSFB4m and normal PperSFB2, and style determinant genes PperS1-RNase, PperS2-RNase, PperS2m-RNase and PperS4-RNase. The mutated PperSFBs encode truncated SFB proteins due to a fragment insertion. The truncated PperSFBs and normal PperSFB2 interacted with PperS-RNases demonstrated by Y2H. Normal PperSFB2 was divided into four parts: box, box-V1, V1-V2 and HVa-HVb. The box domain of PperSFB2 did not interact with PperS-RNases, both of the box-V1 and V1-V2 had interactions with PperS-RNases, while the hypervariable region of PperSFB2 HVa-HVb only interacted with PperS2-RNase showed by Y2H and BiFC assay. Bioinformatics analysis of peach genome revealed that there were other F-box genes located at S-locus, and of which three F-box genes were specifically expressed in pollen, named as PperSLFL1, PperSLFL2 and PperSLFL3, respectively. In phylogenetic analyses PperSLFLs clustered with Pyreae SFBB genes, and PperSFB genes were clustered into the other group with other SFB genes of Prunus. Protein interaction analyses revealed that the three PperSLFLs interacted with PperSSK1 and PperS-RNases with no allelic specificity. In vitro ubiquitination assay showed that PperSLFLs could tag ubiquitin molecules onto PperS-RNases. The above results suggest that three PperSLFLs are the appropriate candidates for the ‘general inhibitor’, which would inactivate the S-RNases in pollen tubes, involved in the self-incompatibility of peach.